Implementation of Reliability Centered Maintenance (RCM) with Fuzzy Logic in Eliminating Off-Hangar Maintenance on Narrow Body Aircraft - Juniawan, Singgih; Jaqin, Choesnul; Prabowo, Herry Agung; Roysen, Uti; Alam, Fachrul; Daruki, Daruki (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
Aircraft maintenance in remote locations is a prevalent challenge for local airlines in Indonesia, leading to diminished productivity and efficiency in the maintenance division. This issue is substantiated by a significant incidence rate of 36% annually, as reported by a national airline. The current solution needed is the improvement of the Maintenance System to eliminate off-hangar maintenance for Narrow Body aircraft in the national aviation service industry. This study aims to identify the causal factors of aircraft requiring maintenance when located outside the primary maintenance facilities and to reduce these occurrences. The Reliability Centered Maintenance (RCM) method is employed to determine the most effective maintenance approach based on system and equipment reliability, and the fuzzy logic method in FMEA is utilized to address ambiguity and uncertainty in risk assessment. Primary data were obtained from Focus Group Discussions (FGD) with experts working in the airline industry. Secondary data were collected from all aircraft experiencing breakdowns outside the main hangar. The findings reveal that the primary factor for maintenance outside the main facilities is the current maintenance policy of Finding Failure (FF), which leads to unpredictable maintenance activities, resulting in damage outside the main facility areas (Batam, Cengkareng, and Surabaya). Incidents of maintenance outside the main facilities can be eliminated by shifting the policy to Time Directed (TD), enabling the company to reduce costs from an initial IDR 342,681,011,118.60 to IDR 70,370,514,198.60, achieving a cost saving of 79.47%.